Strontium titanate ceramic low-temperature brazing connection method
By using vanadate glass powder as the brazing material for ceramic brazing, the residual stress problem caused by the mismatch between the thermal expansion coefficient of the solder and the ceramic is solved, and the effect of low-temperature brazing and high-quality joints is achieved.
Patent Information
- Application Number
- CN202411798690.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
In the existing ceramic brazing connections, the thermal expansion coefficients of the solder and ceramics are different from each other, resulting in a high brazing temperature and a large residual stress inside the joint.
Vanadate glass powder is used as the filler solder. By adjusting the composition of the glass powder (40-50% V2O5, 15-20% B2O3, 20-35% Al2O3 and 3-5% CaO) and preparing method (heating and quenching), the melting point and brazing temperature of the solder are reduced to match the thermal expansion coefficient of the ceramic.
It effectively reduces the residual stress of the joint after brazing, improves the strength and light transmittance of the joint, and realizes low-temperature brazing.
Smart Images

Figure CN119612965A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic brazing, and in particular to a low-temperature brazing connection method for strontium titanate ceramics. Background Art
[0002] Strontium titanate (SrTiO 3 ) Ceramics have excellent dielectric properties and thermal stability and are widely used in chemical, aerospace, electronics and other industries. At present, the main methods for connecting ceramic materials include: transient liquid phase diffusion welding, microwave connection and brazing. Among them, brazing has the characteristics of simple operation and excellent joint performance. Therefore, the present invention adopts this method to connect strontium titanate ceramics.
[0003] The brazing materials for ceramic brazing connection are mainly traditional active metals such as AgCuTi, but due to the large difference in thermal expansion coefficients between active metals and ceramics and high brazing temperature, the residual stress inside the joint is large. Therefore, the present invention introduces a vanadate glass as a filling brazing material. Since the thermal expansion coefficients of the brazing material and ceramics are close and the brazing temperature is low, the residual stress problem of the joint during the cooling process can be reduced to the maximum extent. Summary of the invention
[0004] The main purpose of the present application is to provide a low-temperature brazing connection method for strontium titanate ceramics, aiming to solve the problem of residual stress in the joint caused by the large difference in thermal expansion coefficients between the existing brazing material and the ceramic and the high brazing temperature.
[0005] To achieve the above object, the present application provides a glass powder, the raw materials of the glass powder include the following components according to mass fraction: 40-50% V 2 O 5 15~20%B 2 O 3 、20~35%Al 2 O 3 and 3-5% CaO, the sum of the mass fractions of the above components is 100%.
[0006] To achieve the above object, the present application also provides a method for preparing the above glass powder, comprising: adding 40-50% V 2 O 5 Powder, 15-20% B 2 O 3 Powder, 20-35% Al 2 O 3The invention discloses a method for preparing a glass liquid by mixing MgO powder and 3-5% CaO powder to obtain a mixed powder, wherein the sum of the mass fractions of the above components is 100%; heating the mixed powder to obtain a glass liquid; wherein the heating temperature is 900-1100° C. and the heating time is 1.2-1.6 hours; quenching the glass liquid to obtain glass particles, and crushing the glass particles to obtain glass powder.
[0007] Optionally, when the mixed powder is heated, the heating rate is 5 to 10° C. / min.
[0008] To achieve the above objectives, the present application also provides an application of the above glass powder in low-temperature brazing connection of strontium titanate ceramics.
[0009] To achieve the above-mentioned purpose, the present application also provides a low-temperature brazing connection method for strontium titanate ceramics, comprising: mixing the above-mentioned glass powder with a binder to obtain a glass solder paste; applying the glass solder paste to the surface to be welded of the strontium titanate ceramic to obtain a strontium titanate ceramic to be welded; stacking two strontium titanate ceramics to be welded to obtain a strontium titanate ceramic-glass solder paste-strontium titanate ceramic, which is used as a workpiece to be welded; heating the workpiece to be welded to obtain a brazed strontium titanate ceramic; wherein the heating temperature is 540-650°C and the insulation time is 1-15 minutes.
[0010] Optionally, the heating rate during the heating process is 10° C. / min.
[0011] Optionally, the mass ratio of glass powder to binder is 7 to 10:1.
[0012] Optionally, the binder is terpineol.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The glass powder of the present invention, the vanadium ions in the vanadate glass powder are VO 6 The octahedral form exists in the glass structure, which can effectively reduce the melting point of the solder, thereby achieving low-temperature brazing; vanadate has a wider light transmittance range in the visible and near-infrared regions, which can ensure the light transmittance of strontium titanate ceramics after brazing; B 2 O 3 Slow cooling in the molten state will not crystallize and show excellent glass-forming ability. The low-temperature brazing connection method of strontium titanate ceramics of the present invention uses vanadate glass powder as brazing material. Compared with active brazing material, the thermal expansion coefficient of vanadate glass powder is more matched with the thermal expansion coefficient of strontium titanate ceramics, and the brazing temperature is lower, thereby effectively reducing the residual stress of the joint and improving the joint strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1This is a diagram showing the wetting results of the glass powder on the strontium titanate ceramic obtained in Example 1 of a low-temperature brazing connection method for strontium titanate ceramics of the present application;
[0016] Figure 2 This is a scanning electron microscope morphology image of a joint of a strontium titanate ceramic after brazing obtained in Example 1 of a low-temperature brazing connection method for strontium titanate ceramics of the present application;
[0017] Figure 3 This is a diagram showing the wetting results of the glass powder on the strontium titanate ceramic obtained in Example 2 of a low-temperature brazing connection method for strontium titanate ceramics of the present application;
[0018] Figure 4 This is a diagram showing the wetting results of the glass powder on the strontium titanate ceramic obtained in Comparative Example 1 of a low-temperature brazing connection method for strontium titanate ceramics of the present application;
[0019] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0021] The first embodiment of the present invention provides a glass powder, wherein the raw materials of the glass powder include the following components in terms of mass percentage:
[0022] 40~50%V 2 O 5 15~20%B 2 O 3 、20~35%Al 2 O 3 and 3-5% CaO, the sum of the above components is 100%.
[0023] In this embodiment, the vanadium ions in the vanadate glass powder are in the form of VO 6 The octahedral form exists in the glass structure, which can effectively reduce the melting point of the solder, thereby achieving low-temperature brazing; vanadate has a wider light transmittance range in the visible and near-infrared regions, which can ensure the light transmittance of strontium titanate ceramics after brazing; B 2 O 3It will not crystallize even when slowly cooled from the molten state, and exhibits excellent glass-forming ability. Compared with active brazing materials, the thermal expansion coefficient of vanadate glass is more compatible with that of strontium titanate ceramics, and the brazing temperature is lower, which can reduce the residual stress of the joint to a limited extent and improve the joint strength.
[0024] A second embodiment of the present invention provides a method for preparing glass powder, which specifically comprises the following steps:
[0025] Step S1, according to the mass fraction, 40-50% of V 2 O 5 Powder, 15-20% B 2 O 3 Powder, 20-35% Al 2 O 3 The powder is mixed with 3-5% of CaO powder to obtain a mixed powder, and the mixed powder is heated at 900-1100° C. for 1.2-1.6 hours to obtain a molten glass liquid;
[0026] Specifically, the mixed powder is placed in a platinum crucible, and the crucible is then placed in a muffle furnace, the temperature is increased to 900-1100° C. at a rate of 5-10° C. / min, and the temperature is maintained for 1.2-1.6 hours.
[0027] Step S2, quenching the glass liquid to obtain glass particles, and crushing the glass particles to obtain glass powder.
[0028] A third embodiment of the present invention provides a low temperature brazing connection method for strontium titanate ceramics, comprising the following steps:
[0029] Step S3, mixing the glass powder and the binder at a mass ratio of 7 to 10:1 to obtain a glass solder paste; wherein the binder is pineol;
[0030] Step S4, applying glass solder paste to the surface of the strontium titanate ceramic to be welded, to obtain the strontium titanate ceramic to be welded;
[0031] Before applying the glass solder paste, the strontium titanate ceramic needs to be pretreated. The specific method is: use a diamond cutting machine to cut and shape the strontium titanate ceramic, use 400#, 800#, 1500# and 2000# diamond sand discs to grind it in turn, and finally use anhydrous ethanol to ultrasonically clean it for 15 minutes and then dry it. The coating thickness is 50 to 300μm.
[0032] Step S5, placing two strontium titanate ceramics to be welded in a stack to obtain a strontium titanate ceramic-glass solder paste-strontium titanate ceramic "sandwich structure" as a workpiece to be welded;
[0033] Step S6, heating the workpiece to be welded to obtain a brazed strontium titanate ceramic; wherein the heating rate is 10°C / min, the heating temperature is 540-650°C, and the holding time is 1-15min;
[0034] Specifically, the workpiece to be welded is placed in a muffle furnace and heated to 300°C at a heating rate of 10°C / min, then kept warm for 10 minutes, and then continued to be heated to 540-650°C at a rate of 10°C / min after the insulation is completed, and finally cooled with the furnace to obtain the brazed strontium titanate ceramic.
[0035] Example 1
[0036] Step S1, according to the mass fraction, 45% of V 2 O 5 Powder, 15% B 2 O 3 Powder, 35% Al 2 O 3 The powder is mixed with 5% CaO powder to obtain a mixed powder, the mixed powder is placed in a platinum crucible, the crucible is placed in a muffle furnace, heated to 1100° C. at a heating rate of 5° C. / min, and kept warm for 1.5 hours to obtain a molten glass liquid;
[0037] Step S2, quenching the glass liquid to obtain glass particles, and crushing the glass particles to obtain vanadate glass powder;
[0038] Step S3, mixing vanadate glass powder and pineol at a mass ratio of 10:1 to obtain a glass solder paste;
[0039] Step S4, cutting the strontium titanate ceramic into shape using a diamond cutting machine, polishing it using 400#, 800#, 1500# and 2000# diamond sand discs in sequence, and finally ultrasonically cleaning it with anhydrous ethanol for 15 minutes and then drying it to obtain the pretreated strontium titanate ceramic;
[0040] Step S5, coating the glass solder paste on the surface to be welded of the pretreated strontium titanate ceramic, wherein the coating thickness is 60 μm, to obtain the strontium titanate ceramic to be welded;
[0041] Step S6, placing two strontium titanate ceramics to be welded in a stack to obtain a strontium titanate ceramic-glass solder paste-strontium titanate ceramic "sandwich structure" as a workpiece to be welded;
[0042] Step S7, placing the workpiece to be welded in a muffle furnace, heating it to 300°C at a heating rate of 10°C / min, and then keeping it warm for 10 minutes. After the insulation is completed, continue to heat it to 610°C at a rate of 10°C / min and then keep it warm for 10 minutes. Finally, cool it with the furnace to obtain the brazed strontium titanate ceramic.
[0043] The remaining melt in step S2 of this embodiment is quickly placed in a stainless steel mold at a temperature above 200°C to form a vanadate glass sheet of 5 mm×5 mm×1 mm. The vanadate glass sheet is placed on the pretreated strontium titanate ceramic, and then placed in a muffle furnace, heated to 610°C at a heating rate of 10°C / min, kept warm for 10 minutes, and then cooled with the furnace. The wetting angle at this temperature and holding time is measured to be 45°. Figure 1 It can be seen that the vanadate glass obtained in this example has excellent wettability on strontium titanate ceramics.
[0044] The strontium titanate ceramic brazed joint obtained in this example was characterized using a scanning electron microscope, and the morphology is shown in FIG. Figure 2 It can be seen from the figure that when the glass powder obtained in this embodiment is used as a brazing material to connect strontium titanate ceramics, a high-quality weld without holes or cracks can be obtained. After testing, the shear strength of the joint of strontium titanate ceramics / vanadate glass / strontium titanate ceramics obtained in this embodiment reached 42MPa.
[0045] Example 2
[0046] Step S1, according to the mass fraction, 50% of V 2 O 5 Powder, 20% B 2 O 3 Powder, 25% Al 2 O 3 The powder is mixed with 5% CaO powder to obtain a mixed powder, the mixed powder is placed in a platinum crucible, the crucible is placed in a muffle furnace, heated to 1100° C. at a heating rate of 5° C. / min, and kept warm for 1.5 hours to obtain a molten glass liquid;
[0047] Step S2, quenching the glass liquid to obtain glass particles, and crushing the glass particles to obtain vanadate glass powder;
[0048] Step S3, mixing vanadate glass powder and pineol at a mass ratio of 8:1 to obtain a glass solder paste;
[0049] Step S4, cutting the strontium titanate ceramic into shape using a diamond cutting machine, polishing it using 400#, 800#, 1500# and 2000# diamond sand discs in sequence, and finally ultrasonically cleaning it with anhydrous ethanol for 15 minutes and then drying it to obtain the pretreated strontium titanate ceramic;
[0050] Step S5, coating the glass solder paste on the surface to be welded of the pretreated strontium titanate ceramic, wherein the coating thickness is 50 μm, to obtain the strontium titanate ceramic to be welded;
[0051] Step S6, placing two strontium titanate ceramics to be welded in a stack to obtain a strontium titanate ceramic-glass solder paste-strontium titanate ceramic "sandwich structure" as a workpiece to be welded;
[0052] Step S7, placing the workpiece to be welded in a muffle furnace, heating it to 300°C at a heating rate of 10°C / min, and then keeping it warm for 10 minutes. After the insulation is completed, continue to heat it to 610°C at a rate of 10°C / min and then keep it warm for 10 minutes. Finally, cool it with the furnace to obtain the brazed strontium titanate ceramic.
[0053] The remaining melt in step S2 of this embodiment is quickly placed in a stainless steel mold at a temperature above 200°C to form a vanadate glass sheet of 5 mm×5 mm×1 mm. The vanadate glass sheet is placed on the pretreated strontium titanate ceramic, and then placed in a muffle furnace and heated to 540°C at a heating rate of 10°C / min. After being kept at this temperature for 10 minutes, it is cooled with the furnace. The wetting angle at this temperature and holding time is measured to be 43°. Figure 3 It can be seen that the vanadate glass powder obtained in this example has excellent wettability on strontium titanate ceramics.
[0054] After testing, the shear strength of the joint of strontium titanate ceramic / vanadate glass / strontium titanate ceramic obtained in this embodiment reached 34 MPa.
[0055] Comparative Example 1
[0056] Step S1, according to the mass fraction, 50% of B 2 O 3 Powder, 35% Al 2 O 3 The powder is mixed with 15% CaO powder to obtain a mixed powder, the mixed powder is placed in a platinum crucible, the crucible is placed in a muffle furnace, heated to 1100° C. at a heating rate of 5° C. / min, and kept warm for 1.5 hours to obtain a molten glass liquid;
[0057] Step S2, quenching the glass liquid to obtain glass particles, and crushing the glass particles to obtain vanadate glass powder;
[0058] Step S3, mixing borate glass powder and pineol at a mass ratio of 10:1 to obtain a glass solder paste;
[0059] Step S4, cutting the strontium titanate ceramic into shape using a diamond cutting machine, polishing it using 400#, 800#, 1500# and 2000# diamond sand discs in sequence, and finally ultrasonically cleaning it with anhydrous ethanol for 15 minutes and then drying it to obtain the pretreated strontium titanate ceramic;
[0060] Step S5, coating the glass solder paste on the surface to be welded of the pretreated strontium titanate ceramic, wherein the coating thickness is 60 μm, to obtain the strontium titanate ceramic to be welded;
[0061] Step S6, placing two strontium titanate ceramics to be welded in a stack to obtain a strontium titanate ceramic-glass solder paste-strontium titanate ceramic "sandwich structure" as a workpiece to be welded;
[0062] Step S7, placing the workpiece to be welded in a muffle furnace, heating it to 300°C at a heating rate of 10°C / min, and then keeping it warm for 10 minutes. After the insulation is completed, continue to heat it to 780°C at a rate of 10°C / min and keep it warm for 10 minutes. Finally, cool it with the furnace to obtain the brazed strontium titanate ceramic.
[0063] The remaining melt in step S2 of this embodiment was quickly placed in a stainless steel mold at a temperature above 200°C to form a vanadate glass sheet of 5 mm×5 mm×1 mm. The borate glass sheet was placed on the pretreated strontium titanate ceramic, which was then placed in a muffle furnace and heated to 780°C at a heating rate of 10°C / min. After being kept warm for 10 minutes, the furnace was cooled. The wetting angle at this temperature and holding time was measured to be 73°. Figure 4 , it can be seen that without adding V 2 O 5 The wetting effect of glass powder on ceramics is not ideal.
[0064] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A glass powder, characterized in that: The raw materials of the glass powder include the following components by mass fraction: 40-50% V2O5, 15-20% B2O3, 20-35% Al2O3 and 3-5% CaO, the sum of the mass fractions of the above components is 100%.
2. A method for preparing the glass powder according to claim 1, characterized in that: include: Mixing 40-50% of V2O5 powder, 15-20% of B2O3 powder, 20-35% of Al2O3 powder and 3-5% of CaO powder according to mass fraction to obtain a mixed powder, wherein the sum of the mass fractions of the above components is 100%; The mixed powder is heated to obtain glass liquid; wherein the heating temperature is 900-1100° C. and the heating time is 1.2-1.6 hours; The glass liquid is quenched to obtain glass particles, and the glass particles are crushed to obtain glass powder.
3. The method for preparing glass powder according to claim 2, characterized in that: When the mixed powder is heated, the heating rate is 5-10°C / min.
4. Use of the glass powder as claimed in claim 1 in low temperature brazing connection of strontium titanate ceramics.
5. A low temperature brazing connection method for strontium titanate ceramics, characterized in that: include: Mixing the glass powder according to claim 1 with a binder to obtain a glass solder paste; Applying the glass solder paste to the surface of the strontium titanate ceramic to be welded to obtain the strontium titanate ceramic to be welded; Laying two strontium titanate ceramics to be welded in layers to obtain strontium titanate ceramic-glass solder paste-strontium titanate ceramic, which is used as a workpiece to be welded; The parts to be welded are heated to obtain brazed strontium titanate ceramics; wherein the heating temperature is 540-650° C. and the heat preservation time is 1-15 minutes.
6. The low temperature brazing connection method of strontium titanate ceramics according to claim 5, characterized in that: The heating rate during the heating process was 10°C / min.
7. The low temperature brazing connection method of strontium titanate ceramics according to claim 5, characterized in that: The mass ratio of the glass powder to the binder is 7 to 10:
1.
8. The low temperature brazing connection method of strontium titanate ceramics according to claim 5, characterized in that: The binder is terpineol.
Citation Information
Patent Citations
Glass, glass powder, conductive paste and solar cell
CN110028242A
Glass powder for PERC aluminum paste and preparation method
CN110423012A
Inorganic glass binder for P-type emitter region silver-aluminum electrode paste of N-type silicon solar cell
CN113362981A
Low-temperature sealing composition
JP1995277767A
Glass and dental ceramic
JP1998338540A